Analisis Kualitas Tarif Terhadap Ketertarikan dan Loyalitas Atlet Pencak Silat di Perguruan Silat Garuda Nusantara Kudus - Tito pangesti adji; Naela Khusna Faela Shufa; Muhammad Bagus Binathara (Universitas Aisyah Pringsewu, 2023)
This research aims to find out the level of confidence possessed by pencak silat practitioners there. A combination of qualitative and quantitative methods was used in this descriptive research. The study population was twenty athletes from Pencak Silat Garuda Nusantara Kudus College, and the sample was randomly selected. SPSS.21 was used to analyze data collected using questionnaires. The Garuda Nusantara Kudus Pencak Silat College equipment has an athlete satisfaction level of 70% (good), 30% (moderate), 60% (good), and 40% (moderate). Athletes reported 75% (good) and 25% (fair) satisfaction with the training program, while respondents reported 70% (good) and 30% (moderate) satisfaction with the service. Eight respondents said they were satisfied with university fees, eleven respondents said they were good, and one respondent said they were not good. This shows that the respondents' opinions about cost are very different. Based on the level of loyalty of the respondents to Kolej Pencak Silat Garuda Nusantara Kudus, a total of 15 people out of 20 respondents gave a good response (75%), while 5 people gave a moderate response (25%). The results of the study show that good facilities, reasonable prices, efficient staff, and excellent service have a significant influence on the satisfaction of athletes or customers towards Pencak Silat Garuda Nusantara Kudus College. As a result, the findings of the study regarding the satisfaction of athletes or customers of Pencak Silat Garuda Nusantara Kudus College are very significant.